PENGARUH INFLASI, SUKU BUNGA SBI, PDB DAN NILAI TUKAR TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI BURSA EFEK INDONESIA TAHUN 2000-2014 - Gunawan, Jeffrey Lingga (Arthavidya Jurnal Ilmiah Ekonomi, 2017)
ABSTRACTThis study aimed to analyze the effect of macroeconomic factors consisting of Inflation, Interest Rates SBI, GDP, and Exchange Rate on Jakarta Composite Index (JCI) in Indonesia Stock Exchange Year 2000-2014 as well as to determine which variables are the dominant influence on JCI. Population in this research was the data rate of inflation, interest rates SBI, GDP per capita, the rupiah against the US Dollar and the Jakarta Composite Index (JCI) in Indonesia Stock Exchange from Year 1952 until now, and the sample in this research was the data rate of inflation, interest rates SBI, GDP per capita value of the Rupiah against the US Dollar and the Jakarta Composite Index (JCI) in Indonesia Stock Exchange Year 2000 to 2014. Sampling technique used purposive sampling. Data analyzis was used multiple linear regression. The Year 2000-2014 was chose to limit the scope of the study. The results of this study showed that four independent variables simultaneously influenced changes significantly in JCI. GDP, Interest Rate SBI and rupiah exchange rate was significantly influence JCI, while inflation variable had no significant effect on JCI. The most dominant variable in influencing JCI was GDP.Keywords: Macro Economic Factors, Inflation, Interest Rates, GDP, Exchange Rate, JCI